VARIAN CBR YANG MEWAKILI TERHADAP KEDALAMAN UJI DCP - Muhammad Shalahuddin (Universitas Pasir Pengaraian, 2012)
The relative strength of subgrade where tested by DCP to get the CBR field. DCP test conducted to adepth of 100 cm (long test equipment). Meaning that, the CBR representative is obtained from the relativestrength of the subgrade data to a depth 100 cm. CBR values can also be obtained by laboratory CBR test atsoil samples taken to a depth of 30 cm.Differences in depth review at the DCP test, reading are approaching a depth of 30 cm and 100 cm.CBR representative was calculated at the depth of 30 cm and 100 cm.CBR representative up to a depth of 30 cm was larger than the CBR representative up to a depth of 100cm. CBR representative up to a depth of 30 cm was 1,62 %, CBR representative up to a depth of 100 cm was1,2 %. Soil at a depth 30 cm to 100 cm, naturally have a lower density and CBR.